Behavior of nonionic water soluble homopolymers at the air/water interface: Neutron reflectivity and surface tension results for poly(vinyl methyl ether) - An, S; Thomas, R; Forder, C; Billingham, N; Armes, S; Penfold, J (2002)
The composition and structure of layers of poly(vinylmethyl ether) (PVME) adsorbed at the air/water interface have been determined by neutron reflection and surface tension. For temperatures above and below the cloud point and over most of the range of concentration, neutron reflection gives results in agreement with the Gibbs equation. However, an upturn in the surface tension at low concentrations, which has been observed in several related systems, is attributed to two possible contributions. One is depletion, which has been previously identified by others. The other is polydispersity. At higher concentrations, larger molecular weight species dominate the surface activity and lead to a shallow slope in the surface tension (γ) versus ln(concentration) plot, but at low concentrations smaller molecular weight species increasingly occupy the surface and they give rise to steeper slopes in the γ-In c plot. The segment density profile of PVME normal to the surface is unsymmetrical with a tail extending into the solution. A new method of analyzing reflectivity data that is better able to handle such unsymmetrical distributions is introduced. As the temperature is increased above the cloud point, the adsorbed polymer layer tends to collapse with expulsion of water.